Liquid crystal polymer film, laminate

The introduction of a filler with a low dielectric loss tangent into the liquid crystal polymer film addresses the need for improved dielectric properties in 5G communication systems, resulting in a film with enhanced performance and flexibility.

JP7661161B2Active Publication Date: 2025-04-14FUJIFILM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021116968
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-15
Publication Date
2025-04-14
Estimated Expiration
2041-07-15

AI Technical Summary

Technical Problem

There is a demand for liquid crystal polymer films with improved dielectric properties, specifically a lower dielectric loss tangent, to meet the requirements of advanced 5G mobile communication systems.

Method used

A liquid crystal polymer film is developed that incorporates a filler with a dielectric loss tangent of 0.0020 or less, where the filler occupies at least 10% of the film's volume, and the film is processed to maintain flexibility and prevent cracking.

Benefits of technology

The resulting liquid crystal polymer film achieves a low dielectric loss tangent, enhancing its suitability for high-frequency applications while maintaining flexibility and preventing cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661161000001
    Figure 0007661161000001
  • Figure 0007661161000002
    Figure 0007661161000002
  • Figure 0007661161000003
    Figure 0007661161000003
Patent Text Reader

Abstract

To provide a liquid crystal polymer film low in dielectric tangent and a laminate having a liquid crystal polymer film.SOLUTION: A liquid crystal polymer film containing a liquid crystal polymer and a filler, wherein when the liquid crystal polymer film contains only one type of filler, the dielectric tangent of the filler under conditions of 25°C and a frequency of 10 GHz is 0.0020 or less, when the liquid crystal polymer film contains two or more types of fillers, the mass average value of the dielectric tangent of the two or more types of fillers under conditions of 25°C and a frequency of 10 GHz is 0.0020 or less, and the ratio of the volume that the filler occupies relative to the total volume of the liquid crystal polymer is 10 volume% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to liquid crystal polymer films and laminates. [Background technology]

[0002] The next-generation communication technology, the fifth-generation (5G) mobile communication system, will use higher frequencies and wider bandwidths than ever before. For this reason, substrate films for circuit boards in 5G mobile communication systems are required to have low dielectric constants and low dielectric loss tangents, and development of various materials is underway. One such substrate film is liquid crystal polymer film. Liquid crystal polymer (LCP) film has a lower dielectric constant and lower dielectric loss tangent than films commonly used in fourth-generation (4G) mobile communication systems, such as polyimide films and glass epoxy films.

[0003] For example, Patent Document 1 describes a film made of a liquid crystalline resin composition in which a liquid crystalline polyester composed of specific structural units is blended with spherical silica having a specified average particle size and content of coarse particles and having silanol groups on the surface. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-299254 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, with the increase in processing speed, there is a demand for further improvement in the dielectric properties (eg, dielectric loss) of liquid crystal polymer films used in circuit boards.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a liquid crystal polymer film having a low dielectric tangent. A further object of the present invention is to provide a laminate having a liquid crystal polymer film. [Means for solving the problem]

[0007] As a result of extensive investigation into the above problems, the present inventors have found that the above problems can be solved by the following configuration.

[0008] [1] A liquid crystal polymer film comprising a liquid crystal polymer and a filler, wherein when the liquid crystal polymer film comprises only one type of the filler, the dielectric tangent of the filler is 0.0020 or less at 25°C and a frequency of 10 GHz, and when the liquid crystal polymer film comprises two or more types of the filler, the mass average dielectric tangent of the two or more types of fillers is 0.0020 or less at 25°C and a frequency of 10 GHz, and the ratio of the volume of the filler to the total volume of the liquid crystal polymer film is 10 volume% or more. [2] The liquid crystal polymer film according to [1], wherein the volume ratio of the filler to the total volume of the liquid crystal polymer film is 30 to 60 volume %. [3] The liquid crystal polymer film according to [1] or [2], wherein the liquid crystal polymer film has an X-ray diffraction intensity ratio of 1.07 or less as measured by the method 1 described below. [4] The liquid crystal polymer film according to any one of [1] to [3], wherein the liquid crystal polymer film does not crack when subjected to a bending test by a cylindrical mandrel method using a cylindrical mandrel having a diameter of 8 mm. [5] The liquid crystal polymer film according to any one of [1] to [4], wherein the liquid crystal polymer film has a thickness of 20 to 200 μm. [6] The liquid crystal polymer film according to any one of [1] to [5], wherein when the liquid crystal polymer film contains only one type of the filler, the dielectric loss tangent of the filler at 25°C and a frequency of 10 GHz is lower than the dielectric loss tangent of the liquid crystal polymer at 25°C and a frequency of 10 GHz, and when the liquid crystal polymer film contains two or more types of the fillers, the mass average value of the dielectric loss tangent of the two or more types of fillers at 25°C and a frequency of 10 GHz is lower than the dielectric loss tangent of the liquid crystal polymer at 25°C and a frequency of 10 GHz. [7] The liquid crystal polymer film according to any one of [1] to [6], wherein the filler has a median diameter of 0.1 to 10 μm. [8] The liquid crystal polymer film according to any one of [1] to [7], wherein the filler has a spherical or polyhedral spherical shape and a sphericity of 0.90 or more. [9] The liquid crystal polymer film according to any one of [1] to [8], wherein the filler is inorganic oxide particles or inorganic nitride particles.

[10] The liquid crystal polymer film according to any one of [1] to [9], wherein the filler is a filler that has been surface-treated with a silane coupling agent.

[11] The liquid crystal polymer film according to any one of [1] to

[10] , wherein the volume-based particle size distribution of the filler contained in the liquid crystal polymer film has two or more peaks with different particle sizes.

[12] The liquid crystal polymer film according to any one of [1] to

[11] , wherein the liquid crystal polymer has a dielectric loss tangent of 0.003 or less under conditions of 25° C. and a frequency of 10 GHz.

[13] A laminate comprising the liquid crystal polymer film according to any one of [1] to

[12] and a metal foil. Effect of the Invention

[0009] According to the present invention, it is possible to provide a liquid crystal polymer film having a low dielectric loss tangent. According to the present invention, it is possible to provide a laminate having a liquid crystal polymer film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In the present specification, the notation of groups (atomic groups) that does not indicate whether they are substituted or unsubstituted includes both unsubstituted and substituted groups, unless it is contrary to the spirit of the present invention. For example, an "alkyl group" includes not only an alkyl group that does not have a substituent (unsubstituted alkyl group), but also an alkyl group that has a substituent (substituted alkyl group). In addition, an "organic group" in the present specification refers to a group that contains at least one carbon atom.

[0011] In this specification, when the liquid crystal polymer film is long, the width direction of the liquid crystal polymer film means the short direction and TD (transverse direction), and the length direction means the longitudinal direction and MD (machine direction) of the liquid crystal polymer film. In the present specification, each component may use one substance corresponding to the component alone or two or more substances. Here, when two or more substances are used for each component, the content of the component refers to the total content of the two or more substances, unless otherwise specified. In this specification, the symbol "to" is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, the dielectric loss tangent of the liquid crystal polymer film and the dielectric loss tangent of each component contained in the liquid crystal polymer film are both dielectric loss tangents under conditions of 25° C. and a frequency of 10 GHz. Hereinafter, in this specification, the dielectric loss tangent under conditions of 25° C. and a frequency of 10 GHz is also simply referred to as "dielectric loss tangent".

[0012] The liquid crystal polymer film of the present invention is a liquid crystal polymer film containing a liquid crystal polymer and a filler having a predetermined dielectric tangent, in which the ratio of the volume of the filler to the total volume of the liquid crystal polymer film is 10 volume % or more. Hereinafter, in the liquid crystal polymer film, a better dielectric tangent is also referred to as "the effect of the present invention is better."

[0013] [component] First, the components contained in the liquid crystal polymer film of the present invention will be described.

[0014] [Liquid Crystal Polymer] The liquid crystal polymer film of the present invention comprises a liquid crystal polymer. The liquid crystal polymer is preferably a melt-fabricable liquid crystal polymer.

[0015] The liquid crystal polymer is preferably a thermotropic liquid crystal polymer, which means a polymer that exhibits liquid crystallinity within a certain temperature range. The thermotropic liquid crystal polymer is not particularly limited in terms of its chemical composition as long as it is a liquid crystal polymer that can be melt-molded, and examples thereof include thermoplastic liquid crystal polyesters and thermoplastic polyester amides in which amide bonds have been introduced into thermoplastic liquid crystal polyesters. As the liquid crystal polymer, for example, the thermoplastic liquid crystal polymer described in WO 2015 / 064437 can be used.

[0016] In terms of obtaining superior effects of the present invention, the dielectric loss tangent of the liquid crystal polymer is preferably 0.004 or less, more preferably 0.003 or less, and even more preferably 0.0025 or less. The lower limit is not particularly limited, and may be, for example, 0.0001 or more. In this specification, the term "dielectric loss tangent" for liquid crystal polymers is used to include the "mass average value of the dielectric loss tangents of two or more liquid crystal polymers" when the liquid crystal polymer film contains two or more liquid crystal polymers.

[0017] The dielectric loss tangent of the liquid crystal polymer contained in the liquid crystal polymer film can be measured by the following method. First, the liquid crystal polymer film is immersed in an organic solvent (e.g., pentafluorophenol) of 1000 times the mass of the total mass, and then heated at 120°C for 12 hours to dissolve the organic solvent-soluble components including the liquid crystal polymer into the organic solvent. Next, the eluate including the liquid crystal polymer is separated from the non-eluted components (filler, etc.) by filtration. Next, acetone is added to the eluate as a poor solvent to precipitate the liquid crystal polymer, and the precipitate is separated by filtration. The obtained precipitate is filled into a PTFE (polytetrafluoroethylene) tube (outer diameter 2.5 mm, inner diameter 1.5 mm, length 10 mm), and the dielectric properties are measured by the cavity resonator perturbation method using a cavity resonator (e.g., "CP-531" manufactured by Kanto Electronics Application Development Co., Ltd.) at a temperature of 25°C and a frequency of 10 GHz. The dielectric tangent of the liquid crystal polymer can be obtained by correcting the effect of the voids in the PTFE tube using the Bruggeman equation and the porosity. When a commercially available liquid crystal polymer is used, the value of the dielectric tangent listed in the catalogue of the commercially available product may be used. The porosity (volume ratio of voids in the tube) is calculated as follows. The volume of the space in the tube is calculated from the inner diameter and length of the tube. Next, the weight of the tube before and after filling with the precipitate is measured to calculate the mass of the precipitate filled, and then the volume of the filled precipitate is calculated from the obtained mass and the specific gravity of the precipitate. The volume of the precipitate thus obtained is divided by the volume of the space in the tube obtained above to calculate the filling rate, and the porosity is calculated.

[0018] The liquid crystal polymer may be a commercially available product, such as "LAPEROS" manufactured by Polyplastics, "VECTRA" manufactured by Celanese, "UENO LCP" manufactured by Ueno Pharmaceutical, "Sumikasuper LCP" manufactured by Sumitomo Chemical, "ZYDAR" manufactured by ENEOS, and "Sciberas" manufactured by Toray. Among them, "LAPEROS" manufactured by Polyplastics Co., Ltd. is an example of a liquid crystal polymer having a dielectric tangent value within the above-mentioned preferred range.

[0019] The mass average molecular weight (Mw) of the liquid crystal polymer is not particularly limited, but in terms of superior effects of the present invention, it is preferably from 50,000 to 1,000,000, and more preferably from 100,000 to 500,000. In this specification, the mass average molecular weight is a polystyrene equivalent value measured by gel permeation chromatography (GPC). The GPC measurement was performed using an HLC (registered trademark)-8320GPC (Tosoh Corporation) as a measuring device, two TSKgel (registered trademark) SuperHM-H (6.0 mm ID x 15 cm, Tosoh Corporation) as columns, and an eluent of PFP (pentafluorophenol) / chloroform = 1 / 2 (mass ratio). The measurement conditions were a sample concentration of 0.03 mass%, a flow rate of 0.6 ml / min, a sample injection amount of 20 μL, and a measurement temperature of 40°C, and an RI (differential refractive index) detector was used. The calibration curve is created from eight samples of "Standard sample TSK standard, polystyrene" from Tosoh Corporation: "F-40", "F-20", "F-4", "F-1", "A-5000", "A-2500", "A-1000", and "n-propylbenzene".

[0020] The liquid crystal polymer may be used alone or in combination of two or more kinds. The content of the liquid crystal polymer is not particularly limited, but in terms of better effects of the present invention, the volume of the liquid crystal polymer relative to the total volume of the liquid crystal polymer film is preferably 90 volume % or less, more preferably 80 volume % or less, even more preferably 70 volume % or less, and particularly preferably 60 volume % or less. In addition, in order to improve the flexibility of the liquid crystal polymer film and suppress the occurrence of cracks, breaks, etc. after production, the volume of the liquid crystal polymer relative to the total volume of the liquid crystal polymer film is preferably 30 volume % or more, more preferably 40 volume % or more, and even more preferably 50 volume % or more.

[0021] [Filler] The liquid crystal polymer film of the present invention contains a filler. In the liquid crystal polymer film of the present invention, when the liquid crystal polymer film contains only one type of filler, the dielectric tangent of the filler is 0.0020 or less, and when the liquid crystal polymer film contains two or more types of fillers, the mass average value of the dielectric tangents of the two or more fillers is 0.0020 or less. Hereinafter, unless otherwise specified, the term "dielectric tangent" for a filler is used as a general term including the dielectric tangent of a filler when the liquid crystal polymer film contains only one type of filler, and the mass average value of the dielectric tangents of two or more types of fillers when the liquid crystal polymer film contains two or more types of fillers.

[0022] The volume occupied by the filler relative to the total volume of the liquid crystal polymer film of the present invention (when the liquid crystal polymer film contains two or more types of fillers, the total volume occupied by each filler) is 10 volume % or more. As described above, the liquid crystal polymer film of the present invention contains a predetermined amount of filler having a dielectric loss tangent of 0.0020 or less in addition to the liquid crystal polymer, thereby achieving the effect of the present invention of reducing the dielectric loss tangent.

[0023] In terms of obtaining superior effects of the present invention, the dielectric loss tangent of the filler is preferably 0.0016 or less, and more preferably 0.0012 or less. The lower limit of the dielectric loss tangent of the filler is not particularly limited, and may be 0.0001 or more. As described above, the filler may be used alone or in combination of two or more. When the liquid crystal polymer film contains two or more fillers, the dielectric loss tangent of each filler is preferably 0.0020 or less, more preferably 0.0016 or less, and even more preferably 0.0012 or less. In order to obtain a more excellent effect of the present invention, the dielectric loss tangent of the filler is preferably lower than the dielectric loss tangent of the liquid crystal polymer, and more preferably lower than the dielectric loss tangent of the liquid crystal polymer by 0.0005 or more.

[0024] The dielectric loss tangent of the filler contained in the liquid crystal polymer film can be measured by the following method. First, an organic solvent (e.g., pentafluorophenol) is added in an amount 1000 times the mass of the liquid crystal polymer film, and the film is heated at 120° C. for 12 hours to dissolve the organic solvent-soluble components in the liquid crystal polymer film into the organic solvent in step 1. Then, the organic solvent containing the eluted matter is filtered in step 2 to obtain the filler contained in the liquid crystal polymer film as a filtered residue. Next, the obtained filler is filled into a PTFE tube, and the dielectric properties are measured by a cavity resonator perturbation method using a cavity resonator (e.g., "CP-531" manufactured by Kanto Electronics Application Development Co., Ltd.) at a temperature of 25°C and a frequency of 10 GHz. The dielectric tangent of the filler is obtained by correcting the effect of the voids using the Bruggeman equation and the void ratio. When a commercially available filler is used, the value of the dielectric tangent listed in the catalogue of the commercially available filler may be used.

[0025] In step 1, the liquid crystal polymer film may be pulverized and immersed in an organic solvent to promote dissolution of the soluble components in the liquid crystal polymer. Step 1 is carried out sufficiently until the amount of the organic solvent-soluble components dissolved in the organic solvent becomes constant.

[0026] The volume occupied by the filler relative to the total volume of the liquid crystal polymer film (when the liquid crystal polymer film contains two or more types of fillers, the total volume occupied by each filler) (hereinafter also referred to as the "filler volume fraction") is 10 volume% or more. In terms of the liquid crystal polymer film having a better dielectric tangent and a lower in-plane anisotropy of the liquid crystal polymer, the filler volume fraction is preferably 20% by volume or more, more preferably 30% by volume or more, and even more preferably 40% by volume or more. In terms of improving the flexibility of the liquid crystal polymer film and suppressing the occurrence of cracks, breakage, and the like after production, the filler volume fraction is preferably 60% by volume or less, more preferably 50% by volume or less, and even more preferably 40% by volume or less.

[0027] The type of filler is not particularly limited, but inorganic particles are preferred. Examples of inorganic substances constituting the inorganic particles include oxides such as silica, alumina, magnesium oxide, and zirconia, and nitrides such as aluminum nitride and boron nitride. Examples of organic particles include cross-linked styrene particles and PTFE particles. As the filler, inorganic oxide particles or inorganic nitride particles are preferred, silica particles, alumina particles or boron nitride particles are more preferred, and silica particles are even more preferred. Among the silica particles, crystallized silica particles or fused silica particles are preferred. From the viewpoint of reducing the dielectric loss tangent, crystallized silica particles are more preferred. From the viewpoint of reducing the thermal expansion coefficient, fused silica particles are more preferred.

[0028] The filler may be surface-coated. Examples of the surface treatment agent for the filler include a silane coupling agent. Among them, a filler that has been surface-treated with a silane coupling agent is preferred in terms of improving the dispersibility of the filler and improving the flexibility of the liquid crystal polymer film. That is, it is preferred that a coating layer containing at least one selected from the group consisting of a silane coupling agent (organosilane compound), a partial hydrolyzate thereof, and a condensate thereof is formed on at least a part of the surface of the filler.

[0029] The particle size of the filler is not particularly limited, but the median diameter (D 50 ) is preferably 0.1 to 50 μm, more preferably 0.1 to 10 μm, and further preferably 0.5 to less than 6 μm.

[0030] The median diameter (D 50 ) can be measured using a scanning electron microscope (SEM). Cross sections perpendicular to the film surface are prepared at 10 different locations of a liquid crystal polymer film sample. The cross sections obtained are observed using an SEM at an appropriate magnification of 100 to 100,000 times to obtain observation images. 100 fillers are randomly selected from the obtained observation images, and the periphery of each filler is traced. The particle size of the filler is calculated from these traced images using an image analyzer, and then the particle size at which the total volume is equal on the large diameter side and the small diameter side in the volume-based particle size distribution created from the particle size is calculated to obtain the median diameter (D 50 ) is obtained. When using a commercially available filler, the median diameter (D 50 ) may also be used.

[0031] The filler contained in the liquid crystal polymer film preferably has two or more peaks with different particle sizes in the particle size distribution. In other words, the liquid crystal polymer film preferably contains two or more fillers with different particle sizes. This is because the liquid crystal polymer film contains two or more fillers with different particle sizes, which improves the filling property of the filler and further improves the effects of the present invention. Whether or not the liquid crystal polymer film contains two or more fillers with different particle sizes can be confirmed by whether or not two or more peaks with different particle sizes appear in the particle size distribution measured by the above measurement method. When two or more peaks with different particle sizes appear in the particle size distribution measured by the above measurement method, the particle size distribution indicates that fillers having particle sizes corresponding to each peak are blended into the liquid crystal polymer film. When the liquid crystal polymer film contains two or more fillers with different particle sizes and two or more peaks with different particle sizes appear in the particle size distribution, the median diameter (D 50 ) the particle size of each filler can be obtained. In addition, when a method for manufacturing a liquid crystal polymer film is known and two or more fillers with different particle sizes are used, the catalog values ​​of the commercial products are used as the median diameter (D 50 ) may also be used.

[0032] When the liquid crystal polymer film contains two or more fillers with different particle sizes, the filler with the smaller particle size is selected as the median diameter (D 50 It is preferable that the filler contains at least a filler having a median diameter (D 50 It is more preferable that the filler contains at least a filler having a particle size of 0.5 μm or less. Although there is no particular lower limit, the particle size is preferably 0.1 μm or more from the viewpoint of dispersibility. In addition, when the liquid crystal polymer film contains two or more fillers with different particle sizes, the filler with the larger particle size is selected as the median diameter (D 50 It is preferable that the filler contains at least a filler having a median diameter (D 50 It is more preferable that the filler contains at least a filler having a particle size of 5 μm or more. There is no particular upper limit, and the upper limit is preferably 50 μm or less. That is, when the liquid crystal polymer film contains two or more fillers with different particle sizes, it is preferable to include a combination of a filler having a median diameter of 1 μm or less (more preferably 0.5 μm or less) and a filler having a median diameter of 2 μm or more (more preferably 5 μm or more).

[0033] The shape of the filler is not particularly limited, and may be spherical, ellipsoidal, polyhedral, scaly, or irregular. In terms of superior effects of the present invention, the shape of the filler is preferably spherical or polyhedral. In terms of improving dispersibility and providing better effects of the present invention, the sphericity of the filler is preferably 0.90 or more, and more preferably 0.94 or more. There is no particular upper limit, and the sphericity may be 1.0 or less. Among these, a filler that is spherical or polyhedral spherical and has a sphericity of 0.90 or more is preferred, and a filler that is spherical or polyhedral spherical and has a sphericity of 0.94 or more is more preferred.

[0034] The sphericity of the filler can be calculated from the SEM image of the cross section of the liquid crystal polymer film. Specifically, the projected area (A) and perimeter (M) of the filler particle are measured from the cross-sectional SEM image. If a perfect sphere with perimeter (M) is assumed, its radius (r) is M / 2π, and the area (B) of the assumed perfect sphere is π×(M / 2π). 2 From the projected area (A) and the assumed spherical area (B), the sphericity is A / B=4π×A / M 2 The average value of the sphericity of any 100 filler particles can be used as the sphericity of the filler. When a commercially available product is used as the filler, the catalog value of the commercially available product may be used as the sphericity of the filler.

[0035] [Optional ingredients] The liquid crystal polymer film may contain additives other than the liquid crystal polymer and the filler as optional components, such as a plasticizer, a lubricant, and a heat stabilizer. Examples of the plasticizer include bisphenol compounds (bisphenol A, bisphenol F), alkylphthalyl alkyl glycolate compounds, phosphoric acid ester compounds, and carboxylate compounds. The content of the plasticizer is preferably 0 to 5% by mass based on the total mass of the liquid crystal polymer film. The lubricant may be a fatty acid ester, and the content of the lubricant is preferably 0 to 5% by mass based on the total mass of the liquid crystal polymer film. The heat stabilizer can be selected from phenol-based stabilizers and amine-based stabilizers having a radical scavenging action, phosphite-based stabilizers and sulfur-based stabilizers having a peroxide decomposition action, or hybrid stabilizers having a radical scavenging action and a peroxide decomposition action. The content of the heat stabilizer is preferably 0 to 5% by mass based on the total mass of the liquid crystal polymer film.

[0036] [Characteristics of liquid crystal polymer film] The characteristics of the liquid crystal polymer film will be described below.

[0037] [Thickness] The thickness of the liquid crystal polymer film is preferably from 10 to 300 μm, more preferably from 20 to 200 μm, and further preferably from 50 to 150 μm.

[0038] [X-ray diffraction intensity ratio] The liquid crystal polymer film preferably has a low X-ray diffraction intensity ratio (I1 / I0) measured by the following method. Specifically, the X-ray diffraction intensity ratio (I1 / I0) measured by the following method is preferably 1.10 or less, more preferably 1.07 or less, and even more preferably 1.05 or less. The lower limit is not particularly limited and may be 1.00.

[0039] A method for measuring the X-ray diffraction intensity ratio (I1 / I0), which indicates the in-plane anisotropy of the X-ray diffraction intensity in a liquid crystal polymer film, will be described. Using an X-ray diffraction device, X-rays are irradiated onto the surface of the liquid crystal polymer film, and the X-ray diffraction intensity at 2θ=19° is measured. This X-ray diffraction intensity measurement is performed while rotating the liquid crystal polymer film around the normal direction of the film surface as the rotation axis (β axis). From the measurement results obtained after 360° rotation, the minimum value (I0) and maximum value (I1) of the X-ray diffraction intensity are obtained, and the above-mentioned X-ray diffraction intensity ratio (I1 / I0) is calculated from the ratio of the maximum value (I1) to the minimum value (I0). The X-ray diffraction intensity ratio (I1 / I0) calculated in this way represents the degree of orientation anisotropy of the liquid crystal polymer on the surface of the liquid crystal polymer film.

[0040] Liquid crystal polymers have a rod-like molecular structure, which tends to make them highly oriented. As a result, liquid crystal polymers are often oriented in one direction within the liquid crystal polymer film, and the liquid crystal polymers exhibit anisotropy (orientation anisotropy). On the other hand, when the X-ray diffraction intensity ratio (I1 / I0) of the liquid crystal polymer film is within the above range, the orientation anisotropy of the liquid crystal polymer can be suppressed, and the in-plane anisotropy of the dielectric properties and thermal expansion coefficient can be suppressed. The method for producing a liquid crystal polymer film having an X-ray diffraction intensity ratio (I1 / I0) within the above range and low orientation anisotropy of the liquid crystal polymer is not particularly limited, but an example thereof includes a method for producing a liquid crystal polymer film by melting a coating of a dispersion containing liquid crystal polymer particles and a filler, as described below.

[0041] [Flexibility] The liquid crystal polymer film of the present invention has excellent flexibility, and therefore, even when the liquid crystal polymer film of the present invention is subjected to a bending test by a cylindrical mandrel method using a cylindrical mandrel having a diameter of 16 mm according to the method described in JIS K 5600-5-1, no cracks are generated. For the liquid crystal polymer film, the cylindrical mandrel that does not crack when subjected to the above-mentioned bending test is preferably a cylindrical mandrel with a diameter of 8 mm, more preferably a cylindrical mandrel with a diameter of 4 mm, and even more preferably a cylindrical mandrel with a diameter of 2 mm.

[0042] [Dielectric properties] The liquid crystal polymer film of the present invention has excellent dielectric properties. Specifically, the dielectric loss tangent of the liquid crystal polymer film is preferably 0.0025 or less, more preferably 0.002 or less, and even more preferably 0.0015 or less. The lower limit is not particularly limited, and may be 0.0001 or more. The relative dielectric constant of the liquid crystal polymer film differs depending on the application, but is preferably from 2.0 to 4.0, more preferably from 2.5 to 3.5. The dielectric properties including the dielectric tangent and dielectric constant of the liquid crystal polymer film can be measured by connecting a 10 GHz cavity resonator (Kanto Electronics Application Development Co., Ltd. CP-531) to a network analyzer (Agilent Technology Corp. "E8363B"), inserting a liquid crystal polymer film cut into a strip shape (width: 2.0 mm x length: 80 mm) into the cavity resonator, and using the cavity resonator perturbation method under conditions of a temperature of 25°C and a frequency of 10 GHz.

[0043] [Method of manufacturing liquid crystal polymer film] The method for producing the liquid crystal polymer film is not particularly limited, and examples thereof include the method (casting method) of forming a coating film using the coating solution containing each of the above-mentioned components, drying and heating to produce the above-mentioned liquid crystal polymer film, and the method of extruding the melt obtained by melting each of the above-mentioned components into a film shape using a T-die or extruder to produce a film.The above-mentioned casting method is preferred because it is easy to produce a liquid crystal polymer film with low orientation anisotropy of the liquid crystal polymer. Hereinafter, a method for producing a liquid crystal polymer film will be described by taking the casting method using the above-mentioned coating liquid as an example. In the following description, the liquid crystal polymer film may be simply referred to as a "film".

[0044] The casting method includes, for example, a step A of preparing a coating solution containing a liquid crystal polymer, a filler, and a solvent, a step B of applying the coating solution to a substrate to form a coating film, and a step C of removing the solvent from the coating film. The casting method may also include, after or together with the step C, a step D of melting the liquid crystal polymer contained in the coating film.

[0045] (Process A) In step A, a coating solution containing a liquid crystal polymer, a filler and a solvent is prepared. In the coating solution, the liquid crystal polymer may be dispersed in the solvent, or a part or all of the liquid crystal polymer may be dissolved in the solvent. When at least a part of the liquid crystal polymer is dispersed in the coating solution, it is preferable to carry out step D described below, since a liquid crystal polymer film having a more uniform composition can be produced.

[0046] The solvent is preferably an organic solvent. The organic solvent is not particularly limited, but examples thereof include alcohol-based, ester-based, ketone-based, amide-based and aromatic hydrocarbon-based organic solvents having a boiling point of 60° C. to 250° C., and is appropriately selected from these, taking into consideration the solubility or dispersibility of the liquid crystal polymer and the filler. These solvents may also be mixed solvents obtained by mixing two or more of them.

[0047] The shape of the liquid crystal polymer used in the step A is not particularly limited, but when preparing a coating liquid in which the liquid crystal polymer is dispersed, it is preferable to use a particulate liquid crystal polymer (liquid crystal polymer particles). The shape of the liquid crystal polymer particles is preferably spherical. The median diameter (D 50 ) is preferably 0.1 to 20 μm, more preferably 1 to 10 μm. The median diameter of the liquid crystal polymer particles is measured by a laser diffraction / scattering method using a Microtrac MT3300EXII (manufactured by Nikkiso Co., Ltd.).

[0048] In the step A, the order in which the liquid crystal polymer, the filler, the solvent and any additives are mixed is not particularly limited. In the step A, when the components are mixed, a heating treatment may be carried out within a range that does not affect the properties of the liquid crystal polymer and the filler.

[0049] (Process B) Step B is a step of applying the coating liquid prepared in step A onto a substrate to form a coating film. The coating liquid can be applied by any known method, such as roller coating, gravure coating, knife coating, blade coating, rod coating, dip coating, spray coating, curtain coating, slot coating, and screen printing. The substrate is not particularly limited as long as it has resistance to the liquid crystal polymer solution, but when the film is used as a laminate described later, it is preferable to use a metal foil (more preferably a copper foil) as the substrate.

[0050] (Process C) Step C is a step of removing the solvent from the coating film (coating liquid layer) prepared in step B. The method for removing the solvent is not particularly limited, but it is preferable to evaporate the solvent by methods such as heating, decompression, ventilation, etc. Among them, evaporation by heating is preferable because it has good production efficiency and good operability, and a combination of heating and ventilation is more preferable. As the heating method, known methods such as pressurized steam, heater heating, far-infrared radiation, microwave heating, and heat medium circulation heating can be used.

[0051] (Process D) In terms of improving the film strength, it is preferable to carry out step D, which involves melting the liquid crystal polymer contained in the coating film, after step C. Step D may be carried out simultaneously with step C. That is, the coating film may be heated to melt the liquid crystal polymer contained in the coating film while removing the solvent from the coating film.

[0052] The heating temperature in step D is appropriately adjusted depending on the melting point (Tm) of the liquid crystal polymer, but is preferably 280 to 400° C., more preferably 320 to 400° C. Alternatively, the heating temperature in step D is preferably in the range of 0 to 80° C. higher than the melting point of the liquid crystal polymer, more preferably in the range of 20 to 50° C. higher. The heat treatment time in step D is adjusted appropriately depending on the type of each component, but is preferably from 10 seconds to 60 minutes, and more preferably from 30 seconds to 20 minutes. Moreover, step D is more preferably carried out under an atmosphere of an inert gas such as nitrogen or argon.

[0053] The film with the substrate produced through the above steps A to D may be used as it is, or the film may be used alone after separating the substrate from the film. For example, the film with the metal foil may be immersed in an etching solution to remove the metal foil by etching to produce a film without the substrate. The film may be a single layer, or may have a laminate structure in which a plurality of layers having different compositions are laminated. The produced film may be subjected to a further process of pressing the film with a heated roll to improve the smoothness of the film surface.

[0054] [Applications of liquid crystal polymer film] Examples of applications of the liquid crystal polymer film include film substrates, laminates (flexible laminates) formed by bonding with metal foils, flexible printed wiring boards (FPCs), and laminated circuit boards. In particular, the liquid crystal polymer film is preferably used for a substrate for high speed communication having a liquid crystal polymer film.

[0055] <Laminate> The laminate includes a liquid crystal polymer film and a metal foil, the metal foil being disposed on at least one side of the liquid crystal polymer film, and the liquid crystal polymer film constitutes an electrical insulating layer in the laminate.

[0056] The material used for the metal foil is preferably a metal used for electrical connection. Examples of such metals include copper, gold, silver, nickel, and aluminum, as well as alloys containing these metals. Examples of alloys include copper-zinc alloys, copper-nickel alloys, and zinc-nickel alloys. The metal foil is preferably copper or a copper alloy containing 95% by mass or more of copper. The copper foil may be produced by a rolling method or an electrolysis method. The metal foil may also be subjected to a chemical treatment such as acid washing. The thickness of the metal foil is preferably 4 to 100 μm, more preferably 10 to 35 μm, from the viewpoints of electrical conductivity of the wiring and economic efficiency.

[0057] As a method for producing a laminate of a liquid crystal polymer film and a metal foil, a method of using a metal foil as a substrate when producing a liquid crystal polymer film by the above-mentioned casting method is preferred.In addition, a method of directly forming a metal layer on one surface of a liquid crystal polymer film after producing the liquid crystal polymer film by a method such as vapor deposition, sputtering, plating, etc., and a method of laminating a metal foil on one surface of a liquid crystal polymer film and then thermocompression bonding using a vacuum press device are also included. EXAMPLES

[0058] Examples and comparative examples of the present invention will be described below. The liquid crystal polymer films of Examples 1 to 13 and Comparative Examples 1 and 2 were produced by the production method described below, and were evaluated as described below. First, the production method of the liquid crystal polymer films of each Example and Comparative Example will be described.

[0059] [Raw materials] The raw materials used in the production of the liquid crystal polymer film are shown below. The dielectric tangents of the spherical liquid crystal polymer particles and each filler were measured by the cavity resonator perturbation method according to the above-mentioned method using a cavity resonator (Kanto Electronics Application Development Co., Ltd. CP-531) under conditions of a temperature of 25° C. and a frequency of 10 GHz.

[0060] [Liquid Crystal Polymer] The liquid crystal polymer was prepared in the following manner. After the following raw materials were charged into the polymerization vessel, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 1 hour. After that, the temperature was further raised to 330°C over 3.5 hours, and the pressure was reduced to 10 Torr (i.e., 1330 Pa) over 15 minutes, and polycondensation was carried out while distilling off acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a predetermined value, nitrogen was introduced to change the reduced pressure state to normal pressure and then to pressurized state, and the polymer was discharged from the bottom of the polymerization vessel. The discharged strand was pelletized to obtain pellets of liquid crystal polymer LCP1.

[0061] (raw materials) 4-Hydroxybenzoic acid: 2524g (79.3 mol%) 6-Hydroxy-2-naphthoic acid: 867g (20 mol%) Terephthalic acid (TA): 27 g (0.3 mol%) Metal catalyst (potassium acetate catalyst): 150mg Acylating agent (acetic anhydride): 2336g

[0062] A composition was obtained by melt-kneading 100 parts by mass of the liquid crystal polymer LCP1 obtained in Production Example 1 and 900 parts by mass of polystyrene 1 (manufactured by PS Japan Co., Ltd., "SGP10", glass transition temperature Tg 100°C, melt viscosity 27 Pa s (cylinder temperature 340°C, shear rate 1000 sec-1)) at a cylinder temperature of 340°C and a screw rotation speed of 125 rpm using a twin-screw extruder. The composition was extruded from a circular nozzle at a resin extrusion rate of 10 kg / hr to obtain an extrusion strand, which was then cut and pelletized. 100 g of pellets of the obtained composition were put into 900 g of toluene heated to 40° C. in a 2 L flask and stirred for 30 minutes to dissolve the polystyrene in the toluene. Insoluble components were collected by suction filtration and additionally washed with 90 g of toluene at 40° C. Additional washing was performed three times. The insoluble components after additional washing were filtered through a 1 μm filter, and the filtrate was collected and dried to obtain fine particles (spherical liquid crystal polymer particles) of the liquid crystal polymer (A).

[0063] [Filler] B-1: Crystallized silica particles (manufactured by Nippon Steel Chemical & Material Co., Ltd., spherical (sphericity: 0.98), median diameter (D 50 ) 10μm, dielectric loss tangent 0.0009) B-2: Fused silica particles (Admatechs Co., Ltd. "Admafine SC6500-SQ", spherical (sphericity: 0.95), median diameter (D 50 )2μm, dielectric tangent 0.0011) B-3: Fused silica particles surface-treated with a silane coupling agent having a phenyl group (Admatechs Co., Ltd. "Admafine SC6500-SPD", spherical (sphericity: 0.95), median diameter (D 50 )2μm, dielectric tangent 0.0012) B-4: Fused silica particles (Admatechs Co., Ltd. "Admafine SC2500-SQ", spherical (sphericity: 0.95), median diameter (D 50 ) 0.6μm, dielectric loss tangent 0.0012) B-5: Alumina particles (Sumitomo Chemical Co., Ltd. "Sumicorundum AA-3", polyhedral sphere (sphericity: 0.91), median diameter (D 50)3μm, dielectric tangent 0.0016) B-6: Boron nitride particles (Mizushima Ferroalloy "HP40MF100", irregular particles, median diameter (D 50 ) 40μm, dielectric tangent 0.0007)

[0064] 〔solvent〕 Cyclohexanone

[0065] [Example 1] A liquid crystal polymer film was produced by the following method.

[0066] [Preparation of Dispersion] 28.0 g of the liquid crystal polymer (A), 46.0 g of the filler (B-1), and 57.0 g of cyclohexanone were mixed, and the resulting mixture was subjected to ultrasonic dispersion treatment to prepare dispersion liquid 1.

[0067] [Production of Liquid Crystal Polymer Film] Dispersion 1 was applied to the roughened surface of electrolytic copper foil for flexible copper-clad laminates (Fukuda Metal Foil & Powder Co., Ltd. "CF-T9A-DS-HD2R", thickness 18 μm) using an applicator with a clearance set to 300 μm. After that, it was heated and dried at 100° C. for 3 minutes to obtain copper foil with a coating of Dispersion 1. The copper foil having the coating was then heated at 360° C. for 5 minutes in a nitrogen atmosphere to fuse the particulate liquid crystal polymer contained in the coating. After the heating was completed, the copper foil was naturally cooled to room temperature to obtain a laminate consisting of a liquid crystal polymer film containing crystallized silica particles and the copper foil. The laminate was then immersed in a 40% by mass aqueous solution of iron(III) chloride (Wako Pure Chemical Industries, Ltd.) for 6 hours to etch the copper foil, and then washed with water and dried to obtain a liquid crystal polymer film (thickness 120 μm) containing crystallized silica particles. The ratio of the volume of the filler B-1 to the total volume of the obtained liquid crystal polymer film (filler volume fraction) was 50% by volume.

[0068] [Examples 2 to 13, Comparative Examples 1 and 2] A liquid crystal polymer, a filler and a solvent were mixed so as to obtain the composition shown in Tables 1 and 2 below, and the resulting mixture was subjected to ultrasonic dispersion treatment to prepare dispersions 2 to 15. Filler-containing liquid crystal polymer films of Examples 2 to 13 were produced in the same manner as in Example 1, except that Dispersions 2 to 12 and 15 prepared above were used instead of Dispersion 1, respectively. Moreover, liquid crystal polymer films of Comparative Examples 1 and 2 were produced in the same manner as in Example 1, except that Dispersion 1 was replaced with Dispersion 13 and Dispersion 14 prepared above, respectively. The liquid crystal polymer films of Examples 2 to 13 and Comparative Examples 1 and 2 all had a thickness of 120 μm.

[0069] Tables 1 and 2 show the compositions of dispersions 1 to 15. In the table below, the "Specific Gravity [g / mL]" column indicates the specific gravity (unit: g / mL) of the component listed in the "Component" column.

[0070] [Table 1]

[0071] [Table 2]

[0072] [evaluation] The liquid crystal polymer films of the Examples and Comparative Examples produced by the above-mentioned methods were evaluated for the following characteristics.

[0073] [Dielectric tangent] The dielectric loss tangent of each liquid crystal polymer film was measured under the conditions of a temperature of 25° C. and a frequency of 10 GHz. The dielectric loss tangent was measured by the cavity resonator perturbation method according to the method described above, using a cavity resonator (Kanto Electronics Application Development Co., Ltd., “CP-531”).

[0074] [X-ray diffraction intensity ratio] Using a wide-angle X-ray diffractometer, the in-plane anisotropy of the X-ray diffraction intensity on the surface of each liquid crystal polymer film was measured. Specifically, while rotating the liquid crystal polymer film with the normal direction of the film surface as the rotation axis (β axis), X-rays were irradiated onto the film surface and the X-ray diffraction intensity at 2θ=19° was measured. From the measurement data of the X-ray diffraction intensity obtained by rotating the liquid crystal polymer film 360°, the ratio (I1 / I0) of the maximum value of the X-ray diffraction intensity (I1) to the minimum value of the X-ray diffraction intensity (I0) was calculated. The obtained X-ray diffraction intensity ratio (I1 / I0) indicates the orientation anisotropy of the liquid crystal polymer on the surface of the liquid crystal polymer film.

[0075] [Flexibility] A sample (5 cm x 10 cm strip) of the liquid crystal polymer film of each example and each comparative example was prepared. A bending test was performed on each obtained sample using a cylindrical mandrel bending tester (manufactured by Allgood Co., Ltd.) according to the method described in JIS K 5600-5-1. Cylindrical mandrels with diameters of 32, 16, 8, 4, and 2 mm were used, and the sample was wound around the mandrel, and the presence or absence of cracks (fissures) in the sample was observed. The flexibility of the liquid crystal polymer film was evaluated based on the presence or absence of cracks and the diameter of the mandrel used when the cracks occurred, based on the following evaluation criteria. The smaller the diameter of the mandrel used when cracks occurred, the more flexible the liquid crystal polymer film was.

[0076] (Flexibility Evaluation Criteria) A: No cracks occur in a cylinder with a diameter of 2 mm. B: Cracks occur in the cylinder with a diameter of 2 mm, but no cracks occur in the cylinder with a diameter of 4 mm. C: Cracks occur in the 4 mm diameter cylinder, but no cracks occur in the 8 mm diameter cylinder. D: Cracks occur in the 8 mm diameter cylinder, but no cracks occur in the 16 mm diameter cylinder. E: A crack occurs in a cylinder with a diameter of 16 mm.

[0077] The characteristics and evaluation results of each liquid crystal polymer film are shown in Table 3 below. In the table, the "Dispersion" column indicates the dispersion used, and the "Filler" column indicates the properties of the filler contained in each dispersion. The "Filler volume fraction" column indicates the ratio (unit: volume %) of the volume occupied by the filler to the total volume of each liquid crystal polymer film (if the liquid crystal polymer film contains two or more types of fillers, the total volume occupied by each filler). The "Dielectric loss tangent" column indicates the measured value of the dielectric loss tangent of each liquid crystal polymer film measured by the above method. The column "X-ray diffraction intensity ratio (I1 / I0)" shows the calculation results of the X-ray diffraction intensity ratio (I1 / I0) of each liquid crystal polymer film measured by the above method. The "Flexibility" column indicates the flexibility of each liquid crystal polymer film evaluated by the above method.

[0078] [Table 3]

[0079] From the results shown in the above table, it was confirmed that the liquid crystal polymer film of the present invention can solve the problems of the present invention.

[0080] It was confirmed that the filler volume fraction is preferably 20 volume % or more, more preferably 30 volume % or more, and even more preferably 40 volume % or more, because the dielectric tangent of the liquid crystal polymer film is better and the orientation anisotropy of the liquid crystal polymer is reduced (e.g., comparison of Examples 1 to 6). In addition, in order to obtain a liquid crystal polymer film with better flexibility, it was confirmed that the filler volume fraction is preferably 60 volume % or less, more preferably 50 volume % or less, and even more preferably 40 volume % or less (e.g., comparison between Examples 1 to 6 and 13).

[0081] It was confirmed that a filler having a median diameter of 6 μm or less is more preferable in terms of superior flexibility of the liquid crystal polymer film (eg, comparison between Examples 1 and 7). Also, it was confirmed that the filler that was surface-treated with a silane coupling agent was more preferable in terms of better flexibility of the liquid crystal polymer film (eg, comparison between Examples 1 and 8). In addition, it was confirmed that a liquid crystal polymer film containing two or more fillers with different particle sizes is more preferable in terms of better flexibility of the liquid crystal polymer film (eg, comparison of Examples 1, 8 and 10).

Claims

1. A liquid crystal polymer film comprising a liquid crystal polymer and a filler, the liquid crystal polymer film contains two or more of the fillers, and the mass average value of the dielectric tangent of the two or more fillers at 25° C. and a frequency of 10 GHz is 0.0020 or less; In the volumetric particle size distribution of the filler contained in the liquid crystal polymer film, there are two or more peaks having different particle sizes, the two or more fillers include a combination of a filler having a median diameter of 1 μm or less and a filler having a median diameter of 2 μm or more; The two or more fillers include a filler that has been surface-treated with a silane coupling agent, A liquid crystal polymer film, wherein the ratio of the total volume of the two or more fillers to the total volume of the liquid crystal polymer film is 10 volume % or more.

2. 2. The liquid crystal polymer film according to claim 1, wherein the ratio of the total volume of the liquid crystal polymer film occupied by the two or more kinds of fillers is 30 to 60 volume %.

3. 3. The liquid crystal polymer film according to claim 1, which has an X-ray diffraction intensity ratio of 1.07 or less as measured by the following method 1. Method 1: Using an X-ray diffraction device, X-rays are irradiated from the normal direction to the surface of the liquid crystal polymer film to measure the X-ray diffraction intensity at 2θ = 19°. This measurement of the X-ray diffraction intensity is performed while rotating the liquid crystal polymer film around the normal direction to the film surface as the rotation axis, and the minimum and maximum values ​​of the X-ray diffraction intensity are obtained from the measurement results obtained after 360° rotation, and the X-ray diffraction intensity ratio is calculated from the ratio of the maximum value to the minimum value.

4. The liquid crystal polymer film according to any one of claims 1 to 3, wherein the liquid crystal polymer film does not crack when subjected to a bending test by a cylindrical mandrel method using a cylindrical mandrel having a diameter of 8 mm.

5. The liquid crystal polymer film according to any one of claims 1 to 4, wherein the liquid crystal polymer film has a thickness of 20 to 200 µm.

6. A liquid crystal polymer film described in any one of claims 1 to 5, wherein the mass average value of the dielectric tangent of the two or more types of fillers at 25°C and a frequency of 10 GHz is lower than the dielectric tangent of the liquid crystal polymer at 25°C and a frequency of 10 GHz.

7. 7. The liquid crystal polymer film according to claim 1, wherein the filler has a median diameter of 0.1 to 10 μm.

8. 8. The liquid crystal polymer film according to claim 1, wherein the filler has a spherical or polyhedral shape and a sphericity of 0.90 or more.

9. 9. The liquid crystal polymer film according to claim 1, wherein the filler is an inorganic oxide particle or an inorganic nitride particle.

10. 10. The liquid crystal polymer film according to claim 1, wherein the liquid crystal polymer has a dielectric loss tangent of 0.003 or less under conditions of 25° C. and a frequency of 10 GHz.

11. A laminate comprising the liquid crystal polymer film according to any one of claims 1 to 10 and a metal foil.

Citation Information

Patent Citations

  • High-permittivity resin composition, high-permittivity resin film and capacitor

    JP2004250687A

  • Film comprising liquid crystalline resin composition and manufacturing method thereof

    JP2006299254A

  • Liquid crystal polymer composition, liquid crystal polymer film and laminated product using the same

    JP2007126578A

  • Liquid crystal polyester liquid composition

    JP2012092214A

  • Laminate board and metal base circuit board

    JP2014165485A